2015
DOI: 10.3390/ijerph120911929
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercising in Different Natural Environments on Psycho-Physiological Outcomes in Post-Menopausal Women: A Simulation Study

Abstract: The current study examined potential psycho-physiological benefits from exercising in simulated natural environments among a sample of post-menopausal women using a laboratory based protocol. Participants cycled on a stationary exercise bike for 15 min while facing either a blank wall (Control) or while watching one of three videos: Urban (Grey), Countryside (Green), Coast (Blue). Blood pressure, heart rate and affective responses were measured pre-post. Heart rate, affect, perceived exertion and time percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 66 publications
0
43
1
Order By: Relevance
“…Recreation and physical regeneration are considered basic human needs that can be satisfied by outdoor activities such as walking and jogging (Zeidenitz, 2005;Mönnecke et al, 2006;Arnold et al, 2009). Nature-based recreation provides many benefits, such as physical exercise, aesthetic experiences, intellectual stimulation, and inspiration (Kareiva et al, 2011;Daniel et al, 2012) and has been shown to positively affect an individuals' emotional well-being and health (Bowler et al, 2010;Korpela et al, 2014;White et al, 2015). It is also well documented that people benefit from access to water bodies Kistemann, 2011, 2013;White et al, 2015;Nutsford et al, 2016), especially near-natural rivers (Junker and Buchecker, 2008;Arnold et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recreation and physical regeneration are considered basic human needs that can be satisfied by outdoor activities such as walking and jogging (Zeidenitz, 2005;Mönnecke et al, 2006;Arnold et al, 2009). Nature-based recreation provides many benefits, such as physical exercise, aesthetic experiences, intellectual stimulation, and inspiration (Kareiva et al, 2011;Daniel et al, 2012) and has been shown to positively affect an individuals' emotional well-being and health (Bowler et al, 2010;Korpela et al, 2014;White et al, 2015). It is also well documented that people benefit from access to water bodies Kistemann, 2011, 2013;White et al, 2015;Nutsford et al, 2016), especially near-natural rivers (Junker and Buchecker, 2008;Arnold et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…That people benefit from access to natural and manmade water bodies is well documented (Reinhard and Pouli 2011;Kistemann 2011, 2013). Increasing the visibility of blue space in urban areas has been associated with lower psychological distress (Nutsford et al 2016) and there is evidence that exposure to blue spaces during physical activity shortens perceived exercise duration and increases willingness to repeat such exercise in the future (White et al 2015). Nature-based recreation, aside from the health benefits, has been shown to produce synergistic effects and impact positively on individuals' emotional well-being (Korpela et al 2014;White et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the visibility of blue space in urban areas has been associated with lower psychological distress (Nutsford et al 2016) and there is evidence that exposure to blue spaces during physical activity shortens perceived exercise duration and increases willingness to repeat such exercise in the future (White et al 2015). Nature-based recreation, aside from the health benefits, has been shown to produce synergistic effects and impact positively on individuals' emotional well-being (Korpela et al 2014;White et al 2015). Over 50% of the adult population in the developed world frequently access public waterways for recreational purposes (Williams and Ryan 2004;Environment Agency 2009;Outdoor Foundation 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used the Monitor of Engagement with the Natural Environment (MENE) survey of how people use the natural environment in England which has collected data on over 40,000 individuals per year since 2009. For instance, using data from over 280,000 individuals we estimated that the total amount of physical activity conducted in all natural environments in England had a social value of over £2 billion per year, in terms of Quality Adjusted Life Years (QALYs) [116]. A second study suggested that while local greenspace is positively associated with increased levels of physical activity among dog owners, there is no relationship with non-dog owners [117].…”
Section: Benefits Of Natural Environmentsmentioning
confidence: 99%